2015
DOI: 10.1111/andr.12074
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of novel biomarkers (TLR-2, TLR-4, COX-2, and Nrf-2) of inflammation and oxidative stress in semen of leukocytospermia patients

Abstract: SUMMARYChronic genitourinary inflammation results in Leukocytospermia (LCS), an elevated number of white blood cells (WBCs) in semen, which, in association with oxidative stress, may suppress sperm function, and manifest as male factor infertility. The current clinical diagnosis of LCS employs manual enumeration of WBCs and requires complex staining and laboratory skills or measurement of inflammatory cytokines and chemokines levels. Many patients with idiopathic infertility are asymptomatic. In search of bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 34 publications
(35 reference statements)
4
33
0
Order By: Relevance
“…the fertilization rate of metaphase II oocytes (Moilanen et al, 1998). Although the association between the presence of leukocytes and semen quality or sperm fertility potential is at best questionable, the proposed detrimental effect of leukocytes on spermatozoa is suggested to rely on the ability of leukocytes to release ROS and inflammatory mediators (Aitken & West, 1990;Plante et al, 1994;Whittington & Ford, 1999;Sharma et al, 2001;Henkel et al, 2005;Agarwal et al, 2014;Hagan et al, 2015). Accordingly, ROS are considered the main cause of sperm DNA damage as a consequence of leukocyte infiltration (Aitken et al, 2014).…”
Section: (A) (B) (C) (D)mentioning
confidence: 99%
See 1 more Smart Citation
“…the fertilization rate of metaphase II oocytes (Moilanen et al, 1998). Although the association between the presence of leukocytes and semen quality or sperm fertility potential is at best questionable, the proposed detrimental effect of leukocytes on spermatozoa is suggested to rely on the ability of leukocytes to release ROS and inflammatory mediators (Aitken & West, 1990;Plante et al, 1994;Whittington & Ford, 1999;Sharma et al, 2001;Henkel et al, 2005;Agarwal et al, 2014;Hagan et al, 2015). Accordingly, ROS are considered the main cause of sperm DNA damage as a consequence of leukocyte infiltration (Aitken et al, 2014).…”
Section: (A) (B) (C) (D)mentioning
confidence: 99%
“…Relevant methodological differences in the evaluation of semen leukocyte infiltration and sperm DNA fragmentation may account for the conflicting opinion between those who denied (Henkel et al, 2005;Moskovtsev et al, 2007;present study) or those who advocated (Agarwal et al, 2014;Lobascio et al, 2015) a positive association between sperm DNA fragmentation and the concentration of semen leukocyte. Furthermore, findings cannot be extended to ejaculates with a leukocyte infiltration associated to a symptomatic genital tract infection or to increased levels of inflammatory markers in the seminal plasma (Hagan et al, 2015). These limitations are balanced by the effort to apply an objective method that coupled cytofluorimetry and immunocytochemistry.…”
Section: Limitationsmentioning
confidence: 99%
“…Recently, Ener et al evaluated the oxidative stress status and antioxidant capacity in patients with painful bladder syndrome, and used serum total antioxidant capacity, total oxidant status, binding capacity of exogenous cobalt to human albumin, serum advanced oxidation protein products, paraoxonase, arylesterase, IgE, and C-reactive protein as oxidative markers (17). Some investigators researched the levels of oxidative markers either in urine or semen (18, 19). When compared to these conventional oxidative stress markers, the novel assay developed by Drs.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm cells are well endowed with TLRs [466; 710-712]. However, we can find only one study showing that increased semen expression of TLRs is indeed observed during inflammation and oxidative stress such as occurs during infection and infertility [713]. A more wide-ranging assessment of TLR expression in sperm cells as a function of fertility seems warranted.…”
Section: Toll-like Receptors (Tlrs)mentioning
confidence: 99%